MALL integrated with metacognitive skills to promote preservice English teachers intercultural communicative competence - Haerazi Haerazi (Journal on English as a Foreign Language, 2023)
Utilizing mobile phones for education, particularly in mobile-assisted language learning (MALL), enhances comprehensive learning, intercultural communication, and metacognitive skill development among preservice teachers. This approach fosters the acquisition of intercultural communicative competence (ICC). Therefore, this study aims to investigate the effect of MALL integrated with metacognitive skills to promote preservice English teachers ICC. This pre-experimental study with one group design involved 28 preservice English teachers at a university in Mataram, Indonesia. The ICC and metacognitive questionnaires were utilized to collect the data, and the collected data were analyzed using descriptive and inferential statistical analysis using IBM SPSS devices. The results show that MALL helped preservice English teachers become autonomous learners and actively engage in self-regulating their cognitive abilities to think critically, adapt, and interact within diverse cultural contexts. MALL integrated with metacognitive skills significantly affected preservice teachers ICC, and the level of metacognitive skills influenced the success of improving their ICC. The implication of MALL can delve into the pedagogical approaches and design principles that optimize MALL interventions within mobile learning environments.